+0  
 
0
47
3
avatar+83 

Solve for e.

 

g/e^2-r=m-y

 

I honestly have no clue about the answer for this one

 Jan 16, 2019
 #1
avatar+98044 
+2

I'm assuming that  e^2 - r is in the denominator

 

g / [ e^2 - r ]  = m - y         and we can write

 

[ e^2 - r ] / g  =    1 / [ m - y ]

 

e^2 - r =  g / [ m - y ]

 

e^2 =   g / [ m - y ]  + r

 

e =  ±√ [ g / [ m - y ] + r ]

 

 

cool cool cool

 Jan 16, 2019
 #2
avatar+83 
+1

thanks man, I'll take this information and use it well

Love2Read  Jan 16, 2019
 #3
avatar+83 
0

I need help with 1 more question if you dont mind then I have all the notes I need for my upcoming ACT

Love2Read  Jan 16, 2019

28 Online Users

avatar
avatar
avatar
avatar